Centrally acting antihypertensive agent Ketanserin potential role in delirium management: A review. - Bazzari, Firas Hasan (Open Science Journal, 2017)
Abstract: Delirium is a psychiatric disorder that is well known for being a clinical challenge due to its complex pathophysiology and the wide range of risk factors associated with it. Up to this date, no medical agent is approved by the Food and Drug Administration (FDA) for the treatment of delirium; despite the fact that, a number of clinical guidelines and protocols have recommended the use of some drugs in the management of delirium. Delirium risk factors; predisposing, hospital and acute underlying disease factors, are considered critical points in understanding delirium mechanism. Furthermore, several pathophysiological hypotheses; neurotransmitters imbalance hypothesis, inflammatory hypothesis and structural defects hypothesis, were introduced to explain delirium pathogenesis. Nevertheless, the current evidence is mainly based on and validates the neurotransmitters imbalance theory, since neurotransmitters form the molecular basis of the central nervous system and can be affected by any change occurs in the brain normal conditions. Moreover, pharmacological options introduced as delirium therapies with relative efficacy are mainly based on the neurotransmitters imbalance theory. Ketanserin is a centrally acting antihypertensive agent that has been in the market for over 30 years from now; thus, safety profile is well established. Ketanserin special and unique mechanism of action by inhibiting a wide range of central nervous system receptors; serotonergic (5-HT1D, 5-HT2B, 5-HT2C, 5-HT6), dopaminergic (D1, D2) and adrenergic (α1, α2) receptors, theoretically seems to match with the pathophysiological hypothesis of neurotransmitters imbalance. Moreover, ketanserin might also serve as an empirical therapy for delirium, when the cause of delirium; other than the underlying medical condition, is not determined and an immediate intervention is needed. As it antagonizes almost all the receptors thought to be associated with delirium. Nevertheless, up to this point, it is still a theoretical assumption about the potential role of ketanserin as a pharmacological option in delirium management that needs further investigations to confirm its efficacy.